EXTRACTION, CHARACTERIZATION, AND BIODIESEL POTENTIAL OF PUMPKIN SEED OIL AS A SUSTAINABLE ENERGY RESOURCE - Omale, P.A.; John, O.A.; Joseph, O.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study focused on the extraction and characterization of pumpkin seed oil as a feedstock for biodiesel production, exploring its potential as a sustainable energy resource. Oil was isolated from pumpkin seeds using the solvent extraction method, with hexane selected as the primary solvent due to its high efficiency in extracting oil. The extracted oil was characterized for its physicochemical properties to determine its suitability as a biodiesel feedstock. The result of Tin Layer Chromatography (TLC) for the determination of Fatty Acid Methyl Ester (FAME) and biodiesel purity showed that, the biodiesel produced was pure when compared with ASTM D6751 and EN 14214 standards. The transesterification process, a key step in biodiesel production was conducted using methanol and a base catalyst (potassium hydroxide) which convert pumpkin seed oil into fatty acid methyl esters (FAMEs). The reaction parameters, including molar ratio of methanol to oil, catalyst concentration, temperature, and reaction time was considered to maximize biodiesel yield and purity. The results of the density, API gravity, FFA, pH, flash point, cloud point, pour point and fire points for the pumpkin seed oil and its biodiesel were 0.93 and 0.84 (g/cm3), 3.62 and 3.98 (g/cm3), 32.27 and 28.54 (%), 5.81 and 7.84, 130 and 150 (oC), 20 and -7 (oC), 17 and -8 (oC), 140 and 170 (oC), respectively. The results indicated that, pumpkin seed oil exhibits favorable characteristics for biodiesel production with promising fuel properties, meeting most of the required standards for use in diesel engines. The utilization of pumpkin seeds, often considered agricultural waste when used as biodiesel, adds value to pumpkin and promotes its sustainable practice.